Potensi Ekstrak Daun Kelor dan Air Buah Lontar sebagai pengencer alami dalam Preservasi Semen Babi: Literatur Review - Banamtuan, Adyanto; Mafefa, Nitty Cendrabagusti (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Boar semen preservation is a method of preserving semen that serves to extend its shelf life and increase its volume, thereby impacting the number of females that are inseminated. Preserved semen is directly related to the quality of the diluent used. Patented diluents are the preferred choice for semen dilution, but they are expensive and not always available, so many studies have examined the use of natural diluents for preservation. The purpose of this literature study is to examine the effectiveness of moringa leaf extract and palmyra juice as natural diluents in semen preservation. The method used in this literature study was to collect various updated sources obtained from journals found through Google Scholar, Scopus, and Sinta. The selection of sources was based on their relevance to topics such as moringa leaf extract, palmyra juice, boar semen, preservation, antioxidants, and artificial insemination. Based on the research that has been conducted, moringa leaf extract and palmyra juice provide good results in improving semen quality, particularly in increasing sperm motility and viability, as well as providing an environmentally friendly and affordable alternative diluent for farmers. The use of palmyra juice has been added as a natural diluent that can protect bovine spermatozoa during preservation, while the addition of moringa leaf extract in tris-egg yolk diluent can suppress abnormal sperm abnormalities in sheep during cold storage. Overall, the use of both moringa leaf extract and palmyra juice offers an effective and efficient alternative solution in boar semen preservation for artificial insemination programs